2021
DOI: 10.1111/ajgw.12490
|View full text |Cite
|
Sign up to set email alerts
|

Aeration ofVitis viniferaShiraz fermentation and its effect on wine chemical composition and sensory attributes

Abstract: Background and Aims Aeration during fermentation of red wines has the potential to enhance positive red fruit attributes and suppress less desirable reductive characteristics. The implementation of aeration in commercial winemaking, however, is impeded by the lack of a clear understanding of both the major benefits of its use and the nature of the aeration regimes required to modify the finished product. This work aimed to evaluate the impact of different modes of aeration, varying in their timing, duration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…A post-hoc Tukey test was calculated at a 95% confidence level for attributes showing statistical evidence to have differed across strain effect using the judge by treatment error term. To explore and model the relationships between wine composition and sensory data of the treatment fermentation replicates, Partial Least Squares Regression (PLS-R) was conducted similarly to that described in Day, et al [40]. Briefly, chemical variables (x's) and sensory responses (y's) were standardised, full cross-validation was performed, and the NIPALS algorithm was used with 30,000 iterations calculated.…”
Section: Discussionmentioning
confidence: 99%
“…A post-hoc Tukey test was calculated at a 95% confidence level for attributes showing statistical evidence to have differed across strain effect using the judge by treatment error term. To explore and model the relationships between wine composition and sensory data of the treatment fermentation replicates, Partial Least Squares Regression (PLS-R) was conducted similarly to that described in Day, et al [40]. Briefly, chemical variables (x's) and sensory responses (y's) were standardised, full cross-validation was performed, and the NIPALS algorithm was used with 30,000 iterations calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen management, which includes oxygen exclusion or air addition, is an important tool in winemaking, where it can be used to modify wine aroma, flavor and mouthfeel, and influence wine style [54,55]. Air addition has been shown to increase yeast viability and improve fermentation efficiency [22][23][24][25], at least in white wine production.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of acetate acid was only found to reach 0.84 g/L in the long, higher intensity aerations (total oxygen exposure 20.4 and 49.3 mg L −1 h −1 ). In the same trial, ethyl acetate reached 81 and 102 mg/L compared to Control trial (48 mg/L for no oxygen exposure treatment) (Day et al., 2021).…”
Section: Oxygen (O2)mentioning
confidence: 96%
“…Increasing the redox potential by introducing air during Cabernet Sauvignon wine fermentation at different scales (100‐10,000 L) seems to alleviate the negative sensory characteristics of wines caused by too low reduction potentials, such as hydrogen sulfide (Nelson et al., 2023). In a fermentation study of Shiraz wines, it was found that within the aeration scope studied, not only reductive odors were reduced, but red fruit characteristics were also increased (Day et al., 2021). When the wine is exposed to air, the oxygen concentration is about ∼8 mg/L at room temperature.…”
Section: Oxygen (O2)mentioning
confidence: 99%